2019
DOI: 10.1101/798215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microglial ERK signaling is a critical regulator of pro-inflammatory immune responses in Alzheimer’s disease

Abstract: BackgroundThe mitogen-activated protein kinase (MAPK) pathway is a central regulator of gene expression, pro-survival signaling, and inflammation. However, the importance of MAPK pathway signaling in regulating microglia-mediated neuroinflammation in Alzheimer's Disease (AD) remains unclear. Here we examined the role of MAPK signaling in microglia using pre-clinical in-vitro and in-vivo models of AD pathology integrated with quantitative proteomics studies of postmortem human brains. MethodsWe performed multip… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
(60 reference statements)
2
17
0
Order By: Relevance
“…status also predicts risk of neurodegenerative complications in these conditions. ERK activation in activated microglia has also been implicated in common age-related neurodegenerative disorders such as Parkinson's disease and Alzheimer's disease [36,37]. Our study further demonstrated in vitro a clear causal link between BRAF V600E -induced and ERK-mediated activated microglia and neuronal cell death that does not require physical proximity as in vivo.…”
Section: Discussionsupporting
confidence: 70%
“…status also predicts risk of neurodegenerative complications in these conditions. ERK activation in activated microglia has also been implicated in common age-related neurodegenerative disorders such as Parkinson's disease and Alzheimer's disease [36,37]. Our study further demonstrated in vitro a clear causal link between BRAF V600E -induced and ERK-mediated activated microglia and neuronal cell death that does not require physical proximity as in vivo.…”
Section: Discussionsupporting
confidence: 70%
“…The Ras/MAPK pathway activity is also relevant in glia; for example, microglial phagocytosis requires its activation [ 27 ]. Nevertheless, the Ras/MAPK pathway can also be detrimental to cellular physiology, as it is involved in l -3,4 dihydroxyfenylalanine-( l -DOPA)-treated PD patient dyskinesia.…”
Section: Small Gtpases Of the Ras Familymentioning
confidence: 99%
“…Furthermore, the implication of glial cells should not be disregarded. The description of Ras and Rho GTPases controlling microglial phagocytosis and superoxide generation in AD and PD [ 27 , 86 , 87 , 88 , 98 ] and controlling astrogliosis [ 99 ] has placed glial cells in the focus of many researchers. Therefore, methods specifically targeting glial cells could be a promising therapeutic option.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Our analysis also revealed that the 14-3-3 pathway was altered in Psen1 KI/KI microglia (−log p 9.92), which represent conserved regulatory proteins that act in a variety of cellular processes [28]. Another pathway significantly affected by Psen1 KI/KI was the ERK/MAPK signaling pathway (−log p 9.61) which has been shown to be specifically activated in microglia in a pre-clinical model of AD pathology and human post-mortem AD brains [29]. Interestingly, ERK inhibition reduces the ability of microglia to phagocytose Aβ42 [29].…”
Section: Gene Expression Profiles Of Wt and Psen1 Ki/ki Microgliamentioning
confidence: 99%
“…Another pathway significantly affected by Psen1 KI/KI was the ERK/MAPK signaling pathway (−log p 9.61) which has been shown to be specifically activated in microglia in a pre-clinical model of AD pathology and human post-mortem AD brains [29]. Interestingly, ERK inhibition reduces the ability of microglia to phagocytose Aβ42 [29]. In addition, our analysis revealed that the autophagy pathway was significantly affected by Psen1 KI/KI in microglia (−log p 2.93) ( Fig.…”
Section: Gene Expression Profiles Of Wt and Psen1 Ki/ki Microgliamentioning
confidence: 99%